Application of English law in Malaysia and Singapore: a comparative study / Abdul A'bid Husin … [et al.] - Husin, Abdul A'bid; Roslan, Amirah Khadijah; Mohamed Fazal, Misra Asthana; Ramli, Siti Raudhah (2013)
The principle of this study is to analyse the application of English law in Malaysia and Singapore. Basically, the application of English law in Malaysia is govern by Section 3 and Section 5 of the Civil Law Act 1956. However, these sections have caused some problems to the development of our own law. These problems have been address by a well prominent academicians, legal practitioners and also judges. Furthermore, we will make a comparative study with Singapore legal system in which they have managed to untie their relationship with the Civil Law Act 1956 by repealing Section 5 of the Civil Law Act (Singapore) and enacting the Application of English Law Act 1993 to govern the application of English law in their country. Moreover, we will discuss on the strengths and the weaknesses of the Civil Law Act 1956 (Malaysia) and the Application of English Law Act 1993 (Singapore) in a comprehensive detail. At the end of this paper, we also provide some recommendations to improve the application of English Law in Malaysia which we hope would help in generating our own Malaysian Common Law.